JACKS: joint analysis of CRISPR/Cas9 knockout screens - Allen, Felicity; Behan, Fiona; Khodak, Anton; Iorio, Francesco; Yusa, Kosuke; Garnett, Mathew; Parts, Leopold (Genome Research, 2019)
Genome-wide CRISPR/Cas9 knockout screens are revolutionizing mammalian functional genomics. However, their range of applications remains limited by signal variability from different guide RNAs that target the same gene, which confounds gene effect estimation and dictates large experiment sizes. To address this problem, we report JACKS, a Bayesian method that jointly analyzes screens performed with the same guide RNA library. Modeling the variable guide efficacies greatly improves hit identification over processing a single screen at a time and outperforms existing methods. This more efficient analysis gives additional hits and allows designing libraries with a 2.5-fold reduction in required cell numbers without sacrificing performance compared to current analysis standards.
10.1101/gr.238923.118